Recent advances in modelling masonry shells: Validation and application - Lourenço, Paulo B. (1999)
A composite plasticity model for masonry shells is proposed. Modem algorithmic plasticity concepts - including implicit Euler backward return, mapping schemes and consistent tangent operators for all regimes of the model - are utilised to combine anisotropic elastic behaviour with anisotropic plastic behaviour. The model is capable of reproducing independent (in the sense of completely diverse) elastic and inelastic behaviour along a prescribed set of material axes. An example of the performance of the model is presented, by means of a comparison between numerical results and experimental results for the case of one masonry panel with out-of-plane loading. Examples of the application of the model to solve real engineering problems are also shown.